Sustainable Development Relationships to Culture, Knowledge and Ethics - Parodi, Oliver; Ayestaran, Ignacio; Banse, Gerhard (KIT Scientific Publishing, 2011)
The emergence of a global and technological world and the accelerating dissemination of technology does not only give rise to technological, economic, social, environmental, political and educational tasks. Significant philosophical questions, epistemic reflections and cultural debates result and have to be pushed forward. To move sustainable development from a political mission statement and scientific challenge into everyday life we have to shift our focus of attention to those who are driving a non-sustainable development: human beings and their societal and cultural conditions and interactions. Ultimately not the ecological footprint is the core challenge, but we and those who are leaving this footprint. The idea of the present volume of Sustainable Development - Relationships to Culture, Knowledge and Ethics was developed in the course of the international conference "Sustainability 2010: The Cultural Dimension", which took place in July 2010 in Berlin. The aim of this book is to provide discussions about cultural, epistemic and ethical implications of contemporary changes and emerging challenges on an interdisciplinary and international level.